The views of the fair-minded in the tolerance of Islam to the conquerors of Andalusia - Nouri Shukur, Huda (International Journal of Psychosocial Rehabilitation, 2020)
God Almighty wanted the Nation of Islam to be moderation, that is, based on moderation and tolerance, thus granting multiple and diverse rights to non-Muslims since the dawn of the Islamic call to the present day, and Islam has legalized tolerance away from hostility with the offenders, whether in religion, thought, or politics, and it was a policy. The wise tolerance that the Muslim conquerors followed after the conquest had a great impact on the Islam of a large number of Spaniards. The government of Cordoba did not deviate from the policy of Islamic tolerance, and it never tried to interfere in the affairs of the people of the dhimmah or to object to their beliefs and rituals. And fair Western historians themselves have recognized the tolerance of Muslims, which has been unparalleled, including Thomas Arnold, who says, (But we have not heard about any deliberate attempt to force non-Muslim sects Gustave Le Bon says: (The few writers who have studied the history of the Arabs recognized their moral credit) that Islam looks at humanity with a view of justice and equality and calls for the support of issues of justice and the support of oppressed peoples.